Experimental investigation of thermal performance of novel cold plate design used in a Li-ion pouch-type battery - Kalkan, Orhan; Celen, Ali; Bakirci, Kadir; Dalkilic, Ahmet Selim (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
The world's tendency towards electric vehicles has accelerated and the thermal management of them are critical part of the actual studies. Liquid-based cooling is known as the most common one among other cooling techniques. However, there is still need on the use of various heat transfer enhancement techniques to reduce the maximum temperature and maintain homogenous temperatures. This study experimentally investigated thermal performance of water-cooled cold plates used in thermal management of batteries by using conventional serpentine tube and a novel mini channel designs including a lithium-ion phosphate battery under certain discharge rates from 1C to 5C. Experiments are conducted for different water flow rates from 0.1 to 1.1 L/min as the coolant with inlet temperatures from 15 to 35 degrees C. Experimental results show that lower coolant inlet temperature causes the largest maximum temperature difference on battery surface. The use of mini channel cold plate resulted in 5.7 degrees C reduction in the maximum average battery surface temperature compared to serpentine one. Battery surface temperature homogeneity is improved up to 40% for operating conditions for mini channel cold plate usage. Thus, enhancement on thermal performance of proposed new mini channel cold plate is accomplished by temperature measurements.
Keywords: Battery thermal management system; Cooling; Cold plate design; Mini channel; Li-ion battery; PHASE-CHANGE MATERIALS; MANAGEMENT-SYSTEM; HEAT-PIPE; POWER BATTERY; ELECTRIC VEHICLES; COOLING-PLATE; PACK; OPTIMIZATION; RUNAWAY; ISSUES; Thermodynamics; Energy & Fuels; Engineering; Mechanics